Management and quality sciences as a discussion implicator on the maturity of Polish manufacturers of the agricultural machinery sector = Nauki o zarządzaniu i jakości jako implikator dyskusji o dojrzałości polskich wytwórców sektora maszyn rolniczych - Nogalski, Bogdan; Niewiadomski, Przemysław; Szpitter, Agnieszka A. (Zielona Góra: Faculty of Economics and Management Press)
In the paper, an attempt was made to answer the following question: what is the maturity level of the Polish companies operating in the agricultural machinery sector within the area of the implementation of quality management principles, methods and tools?
Keywords: zarządzanie jakością; dojrzałość przedsiębiorstwa; narzędzia zarządzania jakością; quality management; company maturity; tools of quality management